Dynamic development of gut microbiota and metabolism during and after weaning of kittens - Hong Zhang; Yang Ren; Siyu Wei; Hongli Jin; Yizhen Wang; Mingliang Jin (Animal Microbiome)
Abstract Background As the pet population grows, there is increasing attention on the health and well-being of companion animals. Weaning, a common challenge for young mammals, often leads to issues such as diarrhea, growth retardation, and in severe cases, even mortality. However, the specific changes in gut microbiota and metabolites in kittens following weaning remain unclear. In this study, we conducted a comprehensive investigation of the dynamic changes in the gut microbiota, serum metabolism, antioxidant capacity, and immune function of kittens at various time points: days 0, 4, and 30 post-weaning. Results Significant changes in the immune response and gut microbiota were observed in kittens following weaning. Specifically, IgM levels increased significantly (P < 0.01, n = 20), while IgA and IgG levels showed a sustained elevation. Weaning also disrupted the intestinal microbiota, leading to notable changes in serum metabolism. On day 4 post-weaning, there was a decrease in beneficial bacteria such as Bacteroides vulgatus, Fusobacterium nucleatum, Anaerostipes caccae, and Butyricico-ccaceae. However, by day 30, beneficial bacteria including Candidatus Arthro-mitus, Holdemanella, and Bifidobacterium had increased (P < 0.05, n = 20). Serum metabolites showed clear separation across time points, with day 0 and day 4 exhibiting similar patterns. A total of 45 significantly altered metabolites (P < 0.05, n = 20) were identified, primarily related to vitamins, steroids, peptides, organic acids, lipids, and carbohydrates. Pathway analysis revealed significant enrichment in eight metabolic pathways, with key changes in arginine metabolism and biosynthesis. Additionally, bacteria such as Bacteroides fragilis, Bacteroides stercoris, Leuconostoc citreum, and Bifidobacterium adolescentis were positively correlated with serum metabolic changes, emphasizing the link between gut microbiota and systemic metabolism (P < 0.05, n = 20). Conclusion Our study demonstrated that the composition and function of intestinal microorganisms as well as serum metabolic profiles of weaned kittens presented dynamic changes. These findings not only deepen our understanding of the effects of weaning on kitten health, but also provide valuable insights into post-weaning nutritional regulation strategies for kittens.